PENGARUH KOMPETENSI SISWA DAN PERAN SERTA BKK TERHADAP MOTIVASI UNTUK BEKERJA DI BIDANG OTOMOTIF SISWA KELAS XI JURUSAN TEKNIK KENDARAAN RINGAN SMK SE-KABUPATEN BANTUL - Muhammad Afifi; Sukaswanto Sukaswanto (Universitas Negeri Yogyakarta, 2020)
This study aims to determine: (1) the effect of student competence on the motivation of students of class XI in the Department of Light Vehicle Engineering Vocational Schools in Bantul Regency, and (2) the influence of the participation of BKK on motivation to work in automotive in class XI students of the Department of Light Vehicle Engineering Vocational Schools in Bantul Regency. This research is a comparative associative research. The sampling technique uses proportional random sampling technique. The research sample was 92 students of class XI in Bantul Regency, Department of Light Vehicle Engineering, as many as 92 students. Data collection techniques using tests and questionnaires. The data analysis technique used the Independent t Test. The results of the study showed that (1) Students with high competence had higher motivation to work in the automotive field than students who had low competence as indicated by the tcount greater than the ttable value (6.209 1.973 ), the significance value is smaller than 0.05 (0,000 0.05); and (2) Schools whose BKK participation is active have students with motivation to work in the automotive field higher than students whose BKK participation is less active as indicated by the tcount greater than the ttable value (6,510 1,973), the significance value is smaller of 0.05 (0.006 0.05).